If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -22 = 56 + 4x Reorder the terms: -22 + 6x = 56 + 4x Solving -22 + 6x = 56 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -22 + 6x + -4x = 56 + 4x + -4x Combine like terms: 6x + -4x = 2x -22 + 2x = 56 + 4x + -4x Combine like terms: 4x + -4x = 0 -22 + 2x = 56 + 0 -22 + 2x = 56 Add '22' to each side of the equation. -22 + 22 + 2x = 56 + 22 Combine like terms: -22 + 22 = 0 0 + 2x = 56 + 22 2x = 56 + 22 Combine like terms: 56 + 22 = 78 2x = 78 Divide each side by '2'. x = 39 Simplifying x = 39
| a=2.4c+6 | | 2b+1=b+7 | | y=240+5x | | 3p+21=-6 | | y+140=5x-100 | | 4y-9=43 | | 3y=x-20 | | 5w+3w+4x+5x+10+5=c | | -5x^2+15x+1.7=0 | | x^2+4y^2-2x-24y+21=0 | | 2x^2+20x=-10 | | 12x^7+6x^4-30x^2=0 | | 2(1-y)=8m | | 2X-X-7=-1 | | 7z-3=25 | | 5(2f+3)=6f-15 | | -2(3x-5)=22 | | y=.28-.6x+1.3x-2.9 | | x^2-15x+(56.25)=74.25 | | 8X-2X-5=3+12 | | 93+8=101+93 | | 9x^2+48x+45=0 | | -2(4m-3)=4m | | 9y^2-x^2+4x+18y+5=0 | | 3n+11=-5-n | | (y+2)(y^2-2y+4)= | | 10X+2=-7 | | 9x-5=10+6x | | x+(29+x)+(-13+3*2)=634 | | -100tan^2x+25=0 | | 10sin^2(2x)=5 | | 9-4y=37 |